Enhancing Active Engagement and Metacognitive Development through Padlet Integration in Flipped Learning Environments - Roozafzai, Zahra Sadat (Nexus Publishing NXP, 2025)
Despite the growing emphasis on active learning in higher education, existing research offers limited empirical evidence on the systematic integration of collaborative digital tools, such as Padlet, within flipped learning environments to enhance metacognitive development and student engagement. This study aims to investigate how Padlet can facilitate active learning, self-directed engagement, and the cultivation of metacognitive skills in university classrooms. Employing a mixed-methods design, the research involved 68 undergraduate students enrolled in a flipped learning course at a mid-sized urban university. Quantitative data were collected through pre- and post-intervention surveys measuring engagement and metacognitive awareness, while qualitative insights were gathered via focus group discussions and reflective journals documenting student experiences with Padlet-facilitated activities. Thematic and statistical analyses revealed that integrating Padlet encouraged deeper collaboration, critical reflection, and proactive learning behaviors, while also exposing challenges such as uneven participation, initial technological adaptation hurdles, and occasional cognitive overload during intensive collaborative tasks. The study highlights the importance of structured scaffolding, instructor guidance, and the careful design of digital collaborative activities to maximize learning benefits. These findings provide practical implications for educators seeking to leverage web-based tools to enrich flipped learning pedagogy, enhance metacognitive growth, and foster more engaging, student-centered classroom environments.